PENGARUH KOMUNIKASI DAN SIKAP TERHADAP KEPUTUSAN NASABAH MEMILIH BRI CABANG AHMAD YANI MAKASSAR - Abdul Khalik; Ibrahim H. Ahmad (Jurnal Bisnis dan Kewirausahaan, 2019)
This research is intended to learn to learn attitudes towards customer loyalty and to find out the relationship of communication to loyalty at the ahmad yani makassar branch bri bank. the method of data collection in this study uses data collection methods by submitting questionnaires or questionnaires to understand employee communication and relations with investment loyalty at the ahmad yani branch of makassar bri bank.The analytical method used in this research is the method of multiple regression analysis. The results of the study show that the Communication and Attitudes of Employees show that a creditor's communication skills at the Ahmad Yani Branch of BRI Bank BRI have a positive and significant effect on the decision to choose BRI Ahmad Yani Makassar Branch.The dominant variabel that influences customer loyalty is the attitude of employees.Keywords: Communication, Employee Attitudes and Customer Loyalty